2-Hydroxypropyl-β-cyclodextrin ototoxicity in adult rats: rapid onset and massive destruction of both inner and outer hair cells above a critical dose - Liu, Xiaopeng (Neurotox Res, 2020)
2-hydroxypropyl-β-cyclodextrin (HPβCD), a cholesterol chelator, is being used to treat diseases associated with abnormal cholesterol metabolism such as Niemann-Pick C1 (NPC1) However, the high doses of HPβCD needed to slow disease progression may cause hearing loss. Previous studies in mice have suggested that HPβCD ototoxicity results from selective outer hair cells (OHC) damage. However, it is unclear if HPβCD causes the same type of damage or is more or less toxic to other species such as rats, which are widely used in toxicity research.To address these issues, rats were given a subcutaneous injection of HPβCD between 500 and 4000 mg/kg. Distortion product otoacoustic emissions (DPOAE), the cochlear summating potential (SP) and compound action potential (CAP) were used to assess cochlear function followed by quantitative analysis of OHC and inner hair cell (IHC) loss. The 3000 and 4000 mg/kg doses abolished DPOAE and greatly reduced SP and CAP amplitudes. These functional deficits were associated with nearly complete loss of OHC as well as ~80% IHC loss over the basal two-thirds of the cochlea. The 2000 mg/kg dose abolished DPOAE and significantly reduced SP and CAP amplitudes at the high frequencies. These deficits were linked to OHC and IHC losses in the high-frequency region of the cochlea. Little or no damage occurred with 500 or 1000 mg/kg of HPβCD. The HPβCD-induced functional and structural deficits in rats occurred suddenly, involved damage to both IHC and OHC and was more severe than that reported in mice.